2022
DOI: 10.1007/s11356-022-23362-5
|View full text |Cite
|
Sign up to set email alerts
|

Are natural deep eutectic solvents always a sustainable option? A bioassay-based study

Abstract: The traditional use of organic solvents in various branches of industry is being rethought as these compounds very often display high volatility, toxicity and lipophilicity (related to the ability to interact with biological membranes). More recently, developments in the field of Green Chemistry are focusing on the design of more sustainable and cost-effective solvent alternatives like Ionic Liquids (ILs), bio-based solvents and natural deep eutectic solvents (NADESs). The present study aimed at performing an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 41 publications
(54 reference statements)
1
32
0
Order By: Relevance
“…A caveat on the inadequacy of testing protocols for toxicity has been reported, 16 along with the need for an eco-toxicologic evaluation of DESs scored as “non-toxic” after in vitro tests. 17 The overall message emerging from the literature is to evaluate the impact of the solvent within the frame of the process the solvent is involved in – also including the energy balance in manufacturing, purification, removal and disposal of the solvent – rather than naively attempt an absolute ranking. 18,19 (2) (D)ESs are greener than… As remarked above, a solvent's impact should be assessed within the frame of a synthesis or a process adopting suitable green metrics.…”
Section: The Sustainability Spacementioning
confidence: 99%
“…A caveat on the inadequacy of testing protocols for toxicity has been reported, 16 along with the need for an eco-toxicologic evaluation of DESs scored as “non-toxic” after in vitro tests. 17 The overall message emerging from the literature is to evaluate the impact of the solvent within the frame of the process the solvent is involved in – also including the energy balance in manufacturing, purification, removal and disposal of the solvent – rather than naively attempt an absolute ranking. 18,19 (2) (D)ESs are greener than… As remarked above, a solvent's impact should be assessed within the frame of a synthesis or a process adopting suitable green metrics.…”
Section: The Sustainability Spacementioning
confidence: 99%
“…125 Recently, an ecotoxicological screening showed that NADESs have negligible toxicity to selected marine and freshwater organisms but some degree of biostimulation, suggesting that the accidental release of these compounds may cause excessive growth of microalgae and thus endanger the environment. 126 These data strongly emphasize that the toxicity, biodegradability, and sustainability of a (NA)DES must be scientifically tested and evaluated on a case-by-case basis before widespread use.…”
Section: Deep Eutectic Solvents -Des and Nadesmentioning
confidence: 99%
“…17,29–32 Last but not least, it must be noted that while classic DES display low-to-moderate toxicities – although more studies are needed including the assessment of wide range of the DES components – there is always the risk of eutrophication if large volumes of DES are accidently disposed in the environment, due to the sudden increase in nutrients, that would trigger large biomass production and oxygen depletion in contaminated areas. 13…”
Section: Introduction Deep Eutectic Solvents and Its Holistic Cradle-...mentioning
confidence: 99%
“…11 In that respect, the rst holistic life cycle cradle-to-grave assessments (LCA) of DES have begun to appear in the open literature. 12 Apart from that, other studies have focused on the sustainability of DES, 13,14 its biocompatibility against several (micro) organisms, [15][16][17][18][19][20][21][22][23] and a few studies also on their biodegradability following standard protocols. 17,21,[24][25][26][27] As a result of these investigations, a more realistic picture of the properties of DES and their (allegedly) greenness has emerged.…”
Section: Introduction Deep Eutectic Solvents and Its Holistic Cradle-...mentioning
confidence: 99%
See 1 more Smart Citation